How do 4th, 5th, and 6th grade students' categories of cognitive reflections in interviews on derivational morphology compare to their upper level spelling inventory orthographic knowledge? - Smith, Darcie D (ProQuest Dissertations & Theses, 2012)
Eighty-seven 4th, 5th and 6th grade students were administered the Derivational Relatedness Interview (DRI) (Templeton, Smith, Moloney, Van Pelt, & Ives, 2009). The purpose of this instrument is to explore students' understanding of derivational morphology. During the same week, the subjects were also administered an Upper Level Spelling Inventory (USI), (Bear, Invernizzi, Templeton, & Johnston, 2008). This instrument determines students' level of orthographic development, and also predicts with a significant level of confidence students' reading levels – their comprehension of texts. A mixed methods explanatory design was applied to these existing data used to compare each student's performance on the DRI with their performance on the USI. The DRI interviews were coded for higher level cognitive responses and then compared to each student's performance on the USI. All interviews and USIs are preexisting data. MAXQDA (www.maxqda.com), a computer assisted qualitative data analysis software, was used to code performance on the DRI using L3© a learning level lens developed for this study: Cognitive functions of gist and extrapolation, similarities and differences as indications of good comprehension; filled pauses of four seconds or less, memorized or simple 'yes/no' response answers, and partially correct responses as indications of incomplete comprehension; and unfilled pauses of four seconds or more and wrong/unanswered responses as indications of lacking comprehension. Correlations between the coded categories of the DRI and each student's qualitative spelling inventory (USI) were determined using Pearson r. Results showed a high correlation between the increasing gradients of comprehension as measured by L3 © coding and increasing upper level spelling inventory scores. This high correlation to the USI suggests that student interviews interpreted by coding with L3© parameters might be used as an accurate measure to determine comprehension.